2017
DOI: 10.1167/iovs.17-21756
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Inverted Internal Limiting Membrane Flap in Macular Hole Closure

Abstract: During MH closure, the ILM functioned as a scaffold for the proliferation and migration of Müller cells, and may promote Müller cell activation. Neurotrophic factors and bFGF produced by activated Müller cells and present on the surface of the ILM may contribute to MH closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
128
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(137 citation statements)
references
References 45 publications
5
128
0
4
Order By: Relevance
“…One theory is that the ILM flap may act as a scaffold for glial cells proliferation, resulting in MH filling with proliferating cells, which enhances MH closure. Another explanation might be that the ILM serves as a barrier, disabling the entrance of fluid from the vitreous cavity to the MH [9]. Moreover, the ILM flap is a source of Müller cells, which located at the surface of the ILM flap.…”
Section: Discussionmentioning
confidence: 99%
“…One theory is that the ILM flap may act as a scaffold for glial cells proliferation, resulting in MH filling with proliferating cells, which enhances MH closure. Another explanation might be that the ILM serves as a barrier, disabling the entrance of fluid from the vitreous cavity to the MH [9]. Moreover, the ILM flap is a source of Müller cells, which located at the surface of the ILM flap.…”
Section: Discussionmentioning
confidence: 99%
“…Shiode et al showed that the neurotrophic factors and basic fibroblast growth factors (bFGF) on the surface of the ILM flap promoted the proliferation and migration of the Müller cells, contributing to fill the MH and enhance closure [11]. Activated Müller cells also produced neurotrophic factors and growth factors that may promote the survival of retinal neurons [18]. Moreover, the ILM flaps create a closed compartment enabling the RPE to pump out fluid and keep hole dry [10].…”
Section: Discussionmentioning
confidence: 99%
“…We found that the ILM, which is the basement membrane of Müller cells, functioned as a scaffold to promote the proliferation and migration of glial cells. Furthermore, the activated glial cells produced various neurotrophic factors as well as bFGF [ 20 ]. Therefore, it is reasonable to suppose that the inverted ILM might have acted as a scaffold of embedded glial cells and facilitated the repair process of the macula by glial cells in the current case.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, using an experimental monkey model for large macular hole, we performed an ILM inversion technique and showed that the ILM, which is the basement membrane of Müller cells, was able to facilitate glial cell proliferation and migration as well as the expression of neurotrophic factors and growth factors from glial cells [ 19 ]. This technique thus lead to an acceleration of the wound healing processes at the macula [ 20 ]. Based on these findings, we hypothesized that the ILM might be able to facilitate the therapeutic process of the LHEP embedding technique for the treatment of degenerative LMH.…”
Section: Introductionmentioning
confidence: 99%